2017
DOI: 10.1093/brain/awx086
|View full text |Cite
|
Sign up to set email alerts
|

Right hemisphere structural adaptation and changing language skills years after left hemisphere stroke

Abstract: Language difficulties after stroke are commonly thought to stabilise within a year. Hope et al. report surprising evidence to the contrary, showing that the language skills of patients with post-stroke aphasia continue to change even years after stroke. The changes are associated with structural adaptation in the intact right hemisphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 45 publications
5
72
0
Order By: Relevance
“…Conceptually, regions can be considered a functional extension of each other, just like having a larger functional area which is composed of non-adjacent voxels. The process of functional compensation is thought to be one of the main mechanisms of cognitive recovery after stroke, and, consequently, the "AND" combination is potentially important for considering intervention and recovery mechanisms (R. H. Hope et al, 2017;Piai et al, 2017;Tracy et al, 2014;Turkeltaub et al, 2012) . From an information flow perspective, "AND" combinations can be considered as parallel pathways of information processing into different areas.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, regions can be considered a functional extension of each other, just like having a larger functional area which is composed of non-adjacent voxels. The process of functional compensation is thought to be one of the main mechanisms of cognitive recovery after stroke, and, consequently, the "AND" combination is potentially important for considering intervention and recovery mechanisms (R. H. Hope et al, 2017;Piai et al, 2017;Tracy et al, 2014;Turkeltaub et al, 2012) . From an information flow perspective, "AND" combinations can be considered as parallel pathways of information processing into different areas.…”
Section: Discussionmentioning
confidence: 99%
“…A recent longitudinal study of natural (rather than treatment-induced) recovery in chronic aphasia used voxel based morphometry (VBM) to assess changes in right-hemisphere grey-matter density across two time-points, which in turn were correlated with changes in language functions. 21 Changes in naming accuracy were associated with both increased and decreased right-hemisphere grey matter density in the anterior temporal lobe and the precentral gyrus, respectively. A different, cross-sectional study also showed positive correlations between spoken word comprehension and grey-matter density from VBM in the right middle temporal gyrus and insula and between spoken word production and grey-matter density in the right supplementary motor area cortex and insula.…”
Section: Figurementioning
confidence: 97%
“…For many years, researchers have tried to understand and predict whether and when stroke survivors will recover lost speech and language abilities ( Bang et al, 2005 ; Cloutman et al, 2009 ; Crinion and Price, 2005 ; Hope et al, 2017 ; Hope et al, 2013 ; Konig et al, 2008 ; Lazar et al, 2008 ; Lendrem and Lincoln, 1985 ; Marshall and Phillips, 1983 ; Payabvash et al, 2010 ; Pedersen et al, 1995 ; Seghier et al, 2016 ; Tilling et al, 2001 ; Ween et al, 2000 ). There is broad agreement that lesion location information should play some role in this work ( Plowman et al, 2012 ), but still no consensus on the best or right way to encode that information ( Forkel et al, 2014 ; Hope et al, 2013 ; Mah et al, 2014 ; Price et al, 2017 ; Zhang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%